1990
DOI: 10.1007/bf02530346
|View full text |Cite
|
Sign up to set email alerts
|

Whole-lake food-web manipulation as a means to study community interactions in a small ecosystem

Abstract: Whole-lake food-web manipulation was carried out in the hypertrophic Lake Zwemlust (The Netherlands), with the aim of studying the effects on the lake's trophic status and to gain an insight into complex interactions among lake communities. Before manipulation this small (1.5 ha) and shallow (1.5 m) lake was characterized by Microcystis blooms in summer and high chlorophyll-a concentrations were common (ca. 250/~g 1-1). In March 1987 the planktivorous and benthivorous fish species in the lake were completely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Although this has been explained by the more quiescent environment within the plant beds favouring algae with low sinking rates (Losee & Wetzel, 1993), the same community structure has also been observed in macrophyte-free lakes with high zooplankton grazing pressure, for instance in biomanipulated lakes in which the planktivorous fish stock has been artificially reduced (e.g. Leah, Moss & Forrest, 1980;Reinartsen & Olsen, 1984;Van Donk et al, 1990;Sondergaard et al, 1990). The high contribution of motile forms to the phytoplankton biomass in macrophyte beds may therefore alternatively reflect reduced fish predation.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although this has been explained by the more quiescent environment within the plant beds favouring algae with low sinking rates (Losee & Wetzel, 1993), the same community structure has also been observed in macrophyte-free lakes with high zooplankton grazing pressure, for instance in biomanipulated lakes in which the planktivorous fish stock has been artificially reduced (e.g. Leah, Moss & Forrest, 1980;Reinartsen & Olsen, 1984;Van Donk et al, 1990;Sondergaard et al, 1990). The high contribution of motile forms to the phytoplankton biomass in macrophyte beds may therefore alternatively reflect reduced fish predation.…”
Section: Introductionmentioning
confidence: 85%
“…Thus the phytoplankton community in macrophyte beds is generally dominated by small and motile forms such as cryptophytes, while the abundance of algae with high sinking rates (e.g. diatoms and green algae) is generally low Van Donk et al, 1990). Although this has been explained by the more quiescent environment within the plant beds favouring algae with low sinking rates (Losee & Wetzel, 1993), the same community structure has also been observed in macrophyte-free lakes with high zooplankton grazing pressure, for instance in biomanipulated lakes in which the planktivorous fish stock has been artificially reduced (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming higher settling and lower resuspension rates in smaller lakes, the model of Janse et al (2008) suggested that the thresholds of phosphorus loading for regime shifts should decrease with increasing fetch, but such a prediction evidently does not hold for lakes with area of 0.1-355 km 2 . In the northern temperate zone, mini lakes with area <0.05 km 2 (0.7-1.5 m in depth) were found to be in the clear-water state when TP was 650-2500 mg m À3 (Jeppesen et al, 1990;Van Donk et al, 1990;Carvalho, 1994;Perrow et al, 1994). Such a 'mini-lake phenomenon' may be attributed to various reasons (Jeppesen et al, 1990), among which frequent fish-kills and shallow water depth seem to be most important (Van Geest et al, 2003;Scheffer & van Nes, 2007).…”
Section: à3mentioning
confidence: 99%
“…The efficiency of the small trawl for fry was 45 ~'oNutrient enrichment experiments (bioassays), zooplankton grazing (t4C-tracer technique) and primary production rates were measured to assess the factors limiting the growth of the phytoptankton and to quantify the role of zooplankton grazing. These methods are outlined in Van Donk et aL (1990).…”
Section: Water Chemistry and Biologymentioning
confidence: 99%